Remote sensing of CDOM absorption slope (S275–295) from satellite observations on the West Florida Shelf. (1st December 2018) - Li, Lin; Le, Chengfeng; Cannizzaro, Jennifer; He, Xianqiang
Abstract: Dissolved organic carbon (DOC) plays a critical role in climate-related biogeochemical cycles. The absorption spectrum slope of chromophoric dissolved organic matter (CDOM) in the 275–295 nm spectral range (S275–295 ) have been previously used as indicators of the source, molecular weight, photobleaching, and fate of DOC in estuarine and coastal environments. Here, we developed a multiple regression algorithm using field measurements and near-concurrent satellite observations in estimating S275–295 from satellites in the West Florida Shelf (WFS). The algorithm had a reliable performance in estimating S275–295 in terms of mean relative error and root mean square error < 10%. The algorithm was applied to available daily satellite images to establish long-term time series of S275–295 dynamics and to investigate its driving factors. S275–295 exhibited substantial spatiotemporal variability on the WFS. Correlation analyses revealed that river discharge regulated the temporal and spatial variation of S275–295 on the inner shelf, however, only wind had significant influence on the spatial and temporal distribution of S275–295 on the outer shelf. Climate variations and weather conditions had significant influences on the temporal and spatial distribution of S275–295 on the shelf by influencing the river discharge and wind at short time-scale. Highlights: An empirical algorithm has been developed to derive S275–295 . Long-term S275– 295 time series was established for the West Florida Shelf. Environmental factors forcing S275– 295 dynamics were analyzed.